Associations between on-farm factors and bulk tank SCC on Irish dairy farms - Alice Uí Chearbhaill; Pablo Silva Boloña; Eoin G. Ryan; Catherine I. McAloon; Conor G. McAloon; John Upton (Irish Veterinary Journal)
Abstract Background This study describes associations between bulk tank somatic cell count (BTSCC) and farm management practices, parlour management practices and implemented technologies, milking management practices, somatic cell count (SCC) control strategies, and farmer demographics and attitudes around SCC management using a sample of Irish dairy farms. Results This paper utilised a pre-existing dataset from a farm management and technology survey of 376 commercial Irish dairy farms conducted in 2022. Five mixed models were used to examine associations between variables in each of the five survey sections and log-10 transformed BTSCC (log10BTSCC). Seasonal calving patterns, family members milking alongside survey respondents, and keeping of mastitis treatment records were associated with lower log10BTSCC. Parlour technologies such as automatic cluster removers and automatic washers on the milking machine were associated with significantly reduced log10BTSCC, whereas the presence of backing gates and straight breast rails were associated with increased log10BTSCC. Fore-milking, pre-milking udder preparation and post-milking teat disinfection contributed to lower log10BTSCC. Advice sought from veterinary professionals regarding SCC, multi-faceted approaches to selective dry cow therapy decisions, and utilisation of results from multiple milk recordings were also associated with significantly decreased log10BTSCC. Conclusions In this study, we successfully established associations between log10BTSCC and farm management practices, parlour management practices and implemented technologies, milking management practices, SCC control strategies, and farmer demographics and attitudes around SCC management. We identified scope for further research on many of the aspects found to be associated with log10BTSCC in this study, particularly in the areas of cow positioning within parlours, fore-milking practices, milk recording, and means of disseminating SCC advice to farmers, particularly around the topics of parlour hygiene and selective dry cow therapy.